To find the solution of the system of equations, we can use the method of substitution or elimination.
Let's use the method of substitution:
From the first equation, we have "-3x - 7y = 18".
Solving for x, we have "-3x = 18 + 7y"
or "x = (-18 - 7y)/3".
Substitute this value of x into the second equation:
"9x + 2y = 3" becomes "9((-18 - 7y)/3) + 2y = 3".
Simplifying this equation, we get "-54 - 21y + 6y = 9".
or "-15y = 63".
Solving for y:
"y = -63/15" or "y = -21/5".
Substitute this value of y into the first equation:
"-3x - 7(-21/5) = 18".
Simplifying this equation gives us "-3x + 21(3) = 18".
or "-3x + 63 = 18".
Solving for x, we have "-3x = 18 - 63".
or "x = 45/3" or "x = 15".
So, the solution to the system of equations is x = 15 and y = -21/5.
Find the solution of the system of equations.
minus, 3, x, minus, 7, y, equals, 18
−3x−7y=
18
9, x, plus, 2, y, equals, 3
9x+2y=
3
1 answer